Electronic and thermoelectric properties of alkali metal-based perovskites CsYbF3 and RbYbF3*Two of the authors, Asif Mahmood and S M Ramay, were supported by the Deanship of Scientific Research at King Saud University (Grant No. RGP-311). (November 2020) - Mahmood, Q; Noor, N A; Ghrib, T; Kattan, Nessrin A; Mahmood, Asif; Ramay, Shahid M
Abstract : The electronic and thermoelectric properties of alkali metal-based fluorides CsYbF3 and RbYbF3 are studied by using Wien2k and BoltzTraP codes. The structural and thermodynamic stability of these materials are confirmed by tolerance factor (0.94 and 0.99 for RbYbF3 and CsYbF3 ) and negative formation energy. The optimized lattice constants and bulk moduli are consistent with the results reported in the literature. The reported band gap for RbYbF3 is 0.86 eV which decreases to 0.83 eV by the replacement of Cs with Rb. The electrical and thermal conductivities along with Seebeck coefficients decrease with temperature rising from 0 K to 800 K. The large values of thermoelectric parameters for positive chemical potentials show that the character is dominated by electrons. The studied materials have figures of merit 0.82 and 0.81 at room temperature respectively, for RbYbF3 and CsYbF3 and increase with temperature rising. Therefore, the materials under study may have potential application values in thermoelectric generators and refrigerators.